Dynamic Analysis of Structure Subjected to Bi-Directional and Uni-Directional Earthquake Forces Using ETABS - Subraman, T; Sujatha, S (International Journal of Engineering and Technology, 2018)
When the buildings are are subjected to gravitational and seismic hundreds the larger height acceleration thing is performing in a single course (uni-directional) and with the two additives appearing inside the lateral and within the transverse directions (bi-directional). It’s miles determined that there aren’t any incredible variations among them but the interplay among the bending moments and the axial force inside the yield surfaces is considered. The differences among the responses acquired from the uni- and the bi-directional dynamic loads are evaluated via the usage of etab software and the variations of the buildings subjected to uni and bi-directional horizontal masses mixed with gravitational hundreds are smaller than the variations of responses of these subjected to seismic uni and bi-directional hundreds. in this work we proposed to discover difference and it interference due seismic loading has find out it.